Estrategias comerciales para la difusión de atractivos turísticos de la zona centro sur de Manabí e las agencias de viaje regionales. - Espinoza Castillo, Evelyn M. (2018)
The objective of this work was to develop commercial strategies for the south central area of the province of Manabí, specifically the cantons of Portoviejo, Manta and Puerto López. A three-phase methodology was established under the criteria of IICA I, IICA II, and SECO: The first phase consisted in the analysis of the territory through the collection of basic information for the determination of the tourist system (infrastructure, supra-structure, receiving community, tourism supply and demand) and a SWOT analysis; the tourism market was evaluated for which an analysis of the tourism demand was carried out through the application of surveys to know the profile of the tourist; As for the offer, the managers of the travel agencies were interviewed to identify the tourist trend in the area; It was concluded that the direct competition is the canton of Sucre, since it has characteristics similar to those of the south central zone. The second phase consisted of defining the potential tourist attractions through the results obtained from the evaluation of tourism resources. The compilation of data from the previous phases served to develop marketing strategies, which allow the solution of them, including the creation of new tourism products, the improvement of the quality of existing attractions and the generation of alliances among agencies travel. In the third phase, commercial strategies were formulated for the diffusion of tourist attractions, the proposal that seeks to capture the potential tourist segment for the tourist development of the south central zone.